2018
DOI: 10.1136/sextrans-2017-053376
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for Mycoplasma genitalium endometritis and incident infection: a secondary data analysis of the T cell Response Against Chlamydia (TRAC) Study

Abstract: Objective Assess risk factors for incident and endometrial Mycoplasma genitalium infection and determine if M. genitalium is associated with histological endometritis, an indicator of pelvic inflammatory disease. Methods This study was a secondary data analysis within the T cell Response Against Chlamydia (TRAC) Study, a prospective evaluation of 246 women withor at risk for Chlamydia trachomatis from urban outpatient clinics, who were followed quarterly for12 months. Risk factors for incident M. genitalium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 27 publications
(24 reference statements)
0
12
0
1
Order By: Relevance
“…Recent studies have revealed that inadequate antibiotic coverage against the associated bacteria in chlamydial cervicitis is one of the most prevalent causes of the failure of the treatment. Additionally, some studies indicated that mycoplasma genitalium is one of the most common bacteria associated with chlamydia trachomatis, and moxifloxacin is one of the most effective drugs for the treatment of mycoplasma genitalium (21)(22)(23)(24)48). Based on the reports of some studies, mycoplasma genitalium treatment failed with macrolides such as azithromycin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have revealed that inadequate antibiotic coverage against the associated bacteria in chlamydial cervicitis is one of the most prevalent causes of the failure of the treatment. Additionally, some studies indicated that mycoplasma genitalium is one of the most common bacteria associated with chlamydia trachomatis, and moxifloxacin is one of the most effective drugs for the treatment of mycoplasma genitalium (21)(22)(23)(24)48). Based on the reports of some studies, mycoplasma genitalium treatment failed with macrolides such as azithromycin.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have also reported azithromycin treatment failure (18)(19)(20)(21)(22)(23)(24). In trying to reduce these failures, diagnostic advances are made in relation to chlamydial cervicitis.…”
mentioning
confidence: 99%
“…Chlamydia trachomatis and Neisseria gonorrhoeae were considered the main pathogens in the etiology 43 of PID [1], even if other microorganisms such as Mycoplasma genitalium and anaerobic bacteria were also 44 involved [3,4]. Furthermore, polymicrobial infections were responsible of 30-40% of PID cases [5].…”
Section: Case Studymentioning
confidence: 99%
“…CT is the most prevalent bacterial STI in the United States, and causes significant morbidity, including PID and infertility in young women 22 . Mycoplasma genitalium (MG) is an emerging, highly drug resistant STI, which appears to be more prevalent than gonorrhea, and has been linked to cervicitis and PID in women [23][24][25] , though current CDC guidelines recommend consideration for testing and treatment only in women with persistent cervicitis 26 .…”
mentioning
confidence: 99%